1995
DOI: 10.1093/hmg/4.11.2057
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of mutations in mutator colorectal carcinoma cell lines

Abstract: The nature of mutations occurring in two colorectal carcinoma cell lines deficient in mismatch repair and displaying mutator phenotypes was determined. One of the lines (HCT116) exhibited a higher level of microsatellite instability than the second (DLD-1), although the rate of mutation at the selectable locus encoding the purine salvage enzyme hypoxanthine guanine phosphoribosyl transferase (HPRT) was equally elevated (about 350-450-fold relative to mismatch repair proficient cell lines). Transitions were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 0 publications
6
55
1
Order By: Relevance
“…However, the values of the parental clones T54c10 and T54c4 are between 16 Â and 90 Â the spontaneous MF of lLIZ in somatic tissues of untreated Big Blue mice (lacI reporter system) and a similar lacZ transgenic mouse reporter system, ranging from 2 to 5 Â 10 À5 in several reports (Morrison and Ashby, 1994). The high MF of these clones of DLD1 is due to the defect in the MSH6 MMR gene of this cell line, and similarly, high MF of DLD1 or other MSI colon cancer cells compared with normal diploid fibroblasts has been reported elsewhere using the HPRT or ouabain R endogenously expressed gene systems (Bhattacharyya et al, 1994(Bhattacharyya et al, , 1995. We found that expression of MBD4 tru roughly doubles mutation frequency in cells even on the background of MMR defect, on agreement with the dominant negative hypothesis.…”
Section: Discussionmentioning
confidence: 63%
“…However, the values of the parental clones T54c10 and T54c4 are between 16 Â and 90 Â the spontaneous MF of lLIZ in somatic tissues of untreated Big Blue mice (lacI reporter system) and a similar lacZ transgenic mouse reporter system, ranging from 2 to 5 Â 10 À5 in several reports (Morrison and Ashby, 1994). The high MF of these clones of DLD1 is due to the defect in the MSH6 MMR gene of this cell line, and similarly, high MF of DLD1 or other MSI colon cancer cells compared with normal diploid fibroblasts has been reported elsewhere using the HPRT or ouabain R endogenously expressed gene systems (Bhattacharyya et al, 1994(Bhattacharyya et al, , 1995. We found that expression of MBD4 tru roughly doubles mutation frequency in cells even on the background of MMR defect, on agreement with the dominant negative hypothesis.…”
Section: Discussionmentioning
confidence: 63%
“…These reservations are reinforced by the ®nding that an endogenous expressed gene Dlb-1 had a much higher level of X-ray-induced mutations (mostly involving large deletions) than a bacterial lacI transgene (Sands et al, 1995). Our observations using hprt as a marker gene for deletion mutations contrasts with the high (100 ± 4506) spontaneous hypermutability of the hprt gene in colon cancer cells with genome instability or`replication error' phenotypes (Bhattacharyya et al, 1995;Eshleman et al, 1995) and may appear to be at odds with the earlier observations of very high rates (*10 74 ) of ampli®cation in a drug-resistant gene in p53 7/7 cells (Yin et al, 1992;Bou er et al, 1995). These observations are however based on very dissimilar experimental systems and may not in fact be discordant in their implications.…”
Section: Discussionmentioning
confidence: 78%
“…Remarkably, HNPCC tumours and cell lines derived therefrom are pseudodiploid in stead of aneuploid (Shibata et al, 1994;Kouri et al, 1990;Frei, 1992). They lack one or more DNA repair enzymes (Rhyu, 1996), explaining the multiplicity of mutations, as evidenced by microsatellite instability and by sequencing of genes such as APC, HPRT, TGFb1-RII, IGF,-IIR and p53 (Bhattacharyya et al, 1994(Bhattacharyya et al, , 1995Lazar et al, 1994;Markowitz et al, 1995;Parsons et al, 1995;Souza et al, 1996). These mutations are considered to be relatively early events and they tend to persist during tumour development (Kinzler and Vogelstein, 1996;Rhyu, 1996).…”
Section: Hct-8 Is a Genetically Unstable Cell Linementioning
confidence: 99%
“…Data on the cancer of origin are not available to us but the following arguments indicate that the genetic instability of HCT-8 cells (with the same genetic origin as DLD-1, HCT-15 and HRT-8) is due to a DNA repair de®ciency. Microsatellite instability and a high mutation rate at the HPRT locus was reported for DLD-1 cells (Bhattacharyya et al, 1994(Bhattacharyya et al, , 1995 and ascribed to frameshift mutations in the HMSH6 mismatch repair gene on chromosome 2 (Papadopoulos et al, 1995) and to a heterozygous mutation in the proofreading domain of the DNA polymerase d gene on chromosome 19 (da Costa et al, 1995). We found similar high mutation rates for HPRT as well as for CTNNA1 in HCT-8 cells and the same mutations in the DNA polymerase d and HMSH6.…”
Section: Hct-8 Is a Genetically Unstable Cell Linementioning
confidence: 99%